National policies and regional integration in the South African Development Community - Trudy Hartzenberg; Paul Kalenga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper focuses on the relationship between regional integration in the Southern African Development Community and national policies. Review of trade, industrial, agricultural, labour, and related policy areas, indicates that national policies can and do run counter to the regional integration initiatives that are formalized in the legal instruments of this southern African regional economic community.
Keywords: F13; F15; 330; regional integration; Southern African Development Community